Psychological and social challenges of patients with locally advanced and metastatic gastrointestinal stromal tumours (GIST) on long-term treatment with tyrosine kinase inhibitors: a qualitative study with patients and medical oncologists - Wal, Deborah van de; Fauske, Lena; Bruland, Øyvind S.; Jones, Robin L.; Kasper, Bernd; Wilson, Roger; van der Graaf, Winette T. A.; Husson, Olga (Supportive care in cancer, 2023)
Purpose: Tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of locally advanced and metastatic gastrointestinal stromal tumours (GISTs). Patients are experiencing prolonged survival but often at the expense of their health-related quality of life. It is not only the physical side effects that impact GIST patients’ daily lives but also the psychological and social challenges they have to deal with. This qualitative study aimed to explore the psychological and social life challenges of GIST patients with locally advanced and metastatic disease on ≥ 5 years TKI treatment. Methods: Semi-structured interviews with 15 locally advanced and/or metastatic GIST patients and 10 medical oncologists with experience of delivering care to this specific patient group were conducted. Thematic analysis was used to interpret the data. Results: Psychological challenges expressed by participants concerned fears, scanxiety, negative change in emotion and mood, doubts about their treatment and follow-up, living with uncertainty, lack of understanding from others or healthcare professionals, and constantly being reminded of their illness. Challenges regarding social health included financial difficulties, challenges in relationships, concerns about fertility and parenting, work, and impact on social activities. Conclusion: The reported psychological and social challenges can significantly hamper the overall quality of life of GIST patients. Some challenges were clearly underreported and hardly recognized by medical oncologist, as they may tend to focus on the physical side effects and clinical outcomes of treatment. Therefore, it is essential to take the patient’s perspective into account in research and clinical practice to ensure optimal care for this patient group.